(untitled) (Journal of Science and Technology, 2016)
One fundamental problem faced by the Microfinance industry in Ghana during the period 2003-2007 was the technique adopted for credit risk management by the Microfinance firms (MFFs). This problem prompted this deductive study which was to assess the effectiveness of the techniques adopted by the MFFs to manage their credit risks during that period. The research examined the effectiveness of the techniques used by the firms. It was carried out with the support of a 5-member team from the Institute of Professional Studies, Accra, who assisted during the data collection phase of the study. The study was conducted using 20 Micro-firms in Accra which were randomly selected. The study established that the small MFFs were more vulnerable to credit risk than the bigger firms. The study came out with the recommendations that the MFFs should invest in computerised systems that would enable them compute and assess on a continuous basis, their credit risks track records and generate reports on credits granted. The firms should encourage their clients to insure against risk that might affect their businesses, invest in quality manpower so that they could assess their clients efficiently and help in managing their clients risk bearing portfolio. It was also recommended that the continuous use of written policies that guided most of the firms on credit granting should be encouraged by all the firms.